Using a Massive Open Online Course (MOOC) to promote infection prevention and control learning in healthcare education - Silén-Lipponen, Marja; Koponen, Leena; Korhonen, Ulla; Myllymäki, Mikko (International Journal of Infection Control, 2022)
Background: The prevention of healthcare-associated infections (HAIs) is one of the most important subjects in healthcare education. Aim: The aim of this study was to describe Finnish, Spanish, Portuguese, and Polish healthcare students’ perspectives on learning about HAIs using a Massive Open Online Course (MOOC). This study is part of the Erasmus+ project ‘Educating students for innovative infection prevention and control (IPC) practices in healthcare settings’ (InovSafeCare). Methods: The descriptive cross-sectional research design was used to describe healthcare students’ perspectives on learning about HAIs using the InovSafeCare MOOC (ISC-MOOC). The participants (N = 135) were students recruited from partner institutions. The project group developed a semi-structured questionnaire that was used for data collection, containing questions of technical and pedagogical usability. The data were analyzed by statistical methods and content analysis. Results: The ISC-MOOC facilitated healthcare students’ independent learning and promoted their knowledge of HAI prevention and control. Study materials were easy to use (84%), and the media of the study materials were of high standard (83%). Some technical problems (14%) were also identified with the use of the materials. The study materials were relevant (70%) for IPC learning but should also be provided in different languages. Conclusion: The MOOC will strengthen the role of the students as future healthcare professionals and will also be usable for those healthcare professionals who need to update their skills with today’s HAI requirements. MOOC should also be translated into other languages other than English.